2020
DOI: 10.21203/rs.2.16618/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of cholesterol-assimilating actinomycetes strain and application of statistical modeling approaches for improvement of cholesterol oxidase production by Streptomyces anulatus strain NEAE-94

Abstract: Background: Cholesterol oxidase biosensors have been used to determine the level of cholesterol in different serum and food samples. Due to a wide range of industrial and clinical applications of microbial cholesterol oxidase, isolation and identification of a new microbial source (s) of cholesterol oxidase are very important. Results: The local isolate Streptomyces sp. strain NEAE-94 is a promising source of cholesterol oxidase. It was identified based on cultural, morphological and physiological characterist… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(21 reference statements)
1
0
0
Order By: Relevance
“…The results indicated that PAN 18 and PAN 117 caused partial hemolysis while PAN 9 and PAN 138 led to complete hemolysis of sheep blood erythrocytes. This concurred with previous studies carried out elsewhere El-Naggar and El-Shweihy, 2020). Blood erythrocytes bioassay is extremely sensitive to a wide range of antibiotic extracts from actinomycetes (Soyer and Tanul, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The results indicated that PAN 18 and PAN 117 caused partial hemolysis while PAN 9 and PAN 138 led to complete hemolysis of sheep blood erythrocytes. This concurred with previous studies carried out elsewhere El-Naggar and El-Shweihy, 2020). Blood erythrocytes bioassay is extremely sensitive to a wide range of antibiotic extracts from actinomycetes (Soyer and Tanul, 2020).…”
Section: Discussionsupporting
confidence: 92%